Argentina : Capital Market Assessment and Development Prospects - World Bank Group (World Bank, Washington, DC, 2017)
This report represents a high-level diagnostic of the capital market in Argentina, its potential for corporate, SME and infrastructure financing, and proposed actions to unlock such potential, as well as the respective roles of financial authorities and market participants. A detailed assessment of the government bond market was outside of the scope of the report. However its importance to support the development of the corporate bond market should be highlighted. The report’s findings are based on discussions and information from key representatives of the public sector and a cross section of market participants and other stakeholders. These included representatives from the Ministerio de Finanzas (MoF), the Comisión Nacional de Valores (CNV), the Central Bank (CB), and the Unidad de Información Financiera (UIF). It also met with representatives from the Mercado de Valores de Buenos Aires (MERVAL), the Mercado Argentino de Valores (MAV) the Mercado Abierto Electrónico (MAE), a sample of brokerage houses, banks and fiduciary entities, the Fondo de Garantía de Sustentabilidad (FGS - ANSES), an insurance company, a credit rating agency, a sample of law firms, and a tax firm. The report is organized as follows:  Part One provides a description of the state of development of the market, in particular the supply and demand side. Part Two provides an assessment of critical factors that have an impact on capital market development along with recommendations to address them. Parts Three, Four and Five provide a focused analysis of the use of capital markets for corporate, SME and infrastructure financing.